Lepidoptera of the native forests in the Department of Aluminé (Neuquén-Argentina) - Giganti, Humberto; Dapoto, Graciela; Gentili, Patricia (Bosque (Valdivia), 1994)
In Moquehue, Pilhue and Filcún (Dept. of Aluminé - Neuquén - Argentina) which are part of the north Subantarctic Forests the main tree-species are Araucaria araucana (Mol.) Koch (Araucariaceae) and Nothofagus dombeyi (Mirb.) Oerst., N. pumilio (Poepp. et Endl.) Krasser and N. antarctica (Forster) Oerst. (Fagaceae). Information concerning the entomological fauna and flora of these native forests exploited since the 1950’s for their timber, is scarce. The capture insects were associated with their hosts by observation and bibliography. The Lepidoptera collected belong to 55 species of 11 families, which are associated with Nothofagus spp.: 11, with forest grove vegetation: 17, with native forest species: 3, with exotic forest species: 7. There are 7 poliphagous species (some cosmopolitan) and 22 which do not have identified hosts. Some species, have more than one relationship. Species related with A. araucana were not found.